(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2018)
Ancient Kedah was a port-polity located in the Bujang Valley, an area covering an area spanning from Bukit Choras in the North, the slopes of Jerai Peak, the Merbok-Muda river valleys down to Cherok Tokkun in the South. As a trading port, various foci for commodity exchange flourished in the area, with Pengkalan Bujang being one of them. The area is extremely rich in archaeological remains, consisting of Hindu-Buddhist shrines and icons, dated from the 7thto the 14thCentury C.E. However, discussions regarding the chronology of its position as a trading centre are largely based on the discoveries of tradewares. Since the 1940s, a large number of Chinese ceramics were found, especially during excavations on shrine sites 19, 20, 21-22 and 23. To date, a good number of these ceramics are preserved in the store room of the Bujang Valley Archaeological Museum. This paper presents the preliminary results of the study and documentation on this material. The typological and chronological distributions of these ceramics has given important insights into the development of Pengkalan Bujang from the 9thto the 14thCentury C.E Keywords: Pengkalan Bujang, Chinese Ceramics, Ancient Kedah, Sung Dynasty, Yuan Dynasty